Evaluating the antifungal activity of hempedu bumi (Andrographis Paniculata) on Colletotrichum Gloeosporioides and Aspergillus Niger - Happala Naidu,Shangethaa (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
In agriculture, plant disease caused by fungi commonly affects the crops. Earlier, synthetic fungicides had been applied to inhibit the growth of fungi but eventually they resulted in resistance to some microbes. Presently, herbal plants are being introduced as natural fungicides that provide effective sources to reduce the plant disease. The purpose of this study was to determine if the herbal plant especially Andrographis paniculate exhibit antifungal properties. In order to determine antifungal properties, the A.paniculata plant leaves were extracted using different solvents such as ethanol and hexane. These extracts were screened for antifungal activity by using disc diffusion method with the usage of two fungi namely Aspergillus niger and Colletotrichum gloesoparides. The determination of antifungal activity on A.paniculata was studied by the appearance of inhibition zone around the disc of plates. In screening, ethanol solvent showed good antifungal activity when compared to hexane solvent with 11mm of inhibition zone for A.niger. The parameters that were considered for optimization include incubation time, concentration and fungi used. The best condition postulated for optimization study of ethanol plant extract are 362.74 ppm, 76.51 hours and A.niger fungus with inhibition zone of 13 mm. Therefore, this study showed that A.paniculata has a potential source of being a new antifungal agent.